Materialized views management technology based on work schedule of organizations - Kungurtsev, Oleksii; Vozovikov, Yuri; Kungurtseva, Olena (Eastern-European Journal of Enterprise Technologies, 2013)
There are various software methods of increasing the productivity of informational systems based on using of relational data bases. One of them anticipates using of materialized views. Materialized views stores result of certain request to the data base and at following entry of this request to the informational systems allows getting answer very fast. However the practical use of materialized views in separate informational systems is impossible without preliminary study of this informational system. As materialized views is a result of request which uses number of data bases tables the refreshing of certain data in those tables leads to necessity of refreshing materialized views too. At frequent refreshing of data the using of materialized views could not increase but decrease the effectiveness of informational systems. In this book the periodical connection and disconnection of materialized views is offered. The basis for this is an evident periodicity in resolving of different tasks for the most of organizations.